Efektivitas Penerapan Strategi Everyone is a Teacher Here Untuk Meningkatkan Prestasi Siswa Kelas VIII.A SMPN 1 Gunungsari Pada Mata Pelajaran IPA - Ukir, Lalu Ukir (Hydrogen: Jurnal Kependidikan Kimia, 2019)
This research was conducted at Gunungsari 1 Public Middle School with the aim of knowing the effectiveness of the use of Everyone is A Teacher Here strategy in learning activities, so that how far the results of student learning achievement improved by using the learning strategy. This type of research is classroom action research (CAR) ), which is carried out by the cycle of persiklus with several stages, namely: planning, implementation, observation and reflection. The data in this study are student learning activities and student learning outcomes. The results of the study showed that the application of Beajar Everyone is a Teacher Here strategy was effective to improve students’ learning achievement in grade VIII.A from cycle I to cycle II with an average score of 70 , 48 in the first cycle to 77.27, and classical completeness from the first cycle to the second cycle experienced a significant increase of 59.38 to 87.5 while the results of the analysis of the N-Gain test were 0.32 with the moderate category. Conclusions from the results of the study this is the application of the learning strategy Everyone is a Teacher Here effectively increases the learning activities of Gunungsari 1 Junior High School students in class VIII.A so that learning is more focused, absorbs more subject matter and is more fun for students. So it can be concluded that the application of Everyone’s a Teacher Here learning strategy can effectively improve science learning achievement of students of Gunungsari 1 Junior High School class VIII.A from cycle I to cycle II.